1979
DOI: 10.1042/bj1770951
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of adduct formation between NAD+ and pyruvate bound to pig heart lactate dehydrogenase

Abstract: 1. The rate of adduct formation between NAD+ and enol-pyruvate at the active site of lactate dehydrogenase is determined by the rate of enolization of pyruvate in solution. 2. The proportion of enol-pyruvate solutions is less than 0.01%. 3. The overall dissociation constant of adduct formation is less than 5 X 10(-8) M for pig heart lactate dehydrogenase at pH 7.0. 4. The unusual kinetics for adduct formation previously observed in the case of rabbit muscle lactate dehydrogenase [Griffin & Criddle (1970) Bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our results indicate that the inhibitory effect of pyruvate is highly dependent on pH, and, as Cleland (1970) indicated, this effect can be considered to be uncompetitive. Results obtained recently by us (D. De Arriaga, J. Soler & E. Cadenas, unpublished work) are compatible with the proposal that an abortive ternary complex involving enzyme, NAD+ and pyruvate is responsible for this inhibition, in the same manner as proposed by several authors (Sugrobova et al, 1975;Wilton, 1979;Trommer et al, 1979;). Moreover, we found that the inhibitory effect of pyruvate depends also on the temperature, a fact that has been reported for lactate dehydrogenase from several sources (Somero, 1973;Eichner & Kaplan, 1977;Kao & Farley, 1978), and also on NADH concentration in such a way that inhibition of lactate dehydrogenase should increase with an increased concentration of NADH.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that the inhibitory effect of pyruvate is highly dependent on pH, and, as Cleland (1970) indicated, this effect can be considered to be uncompetitive. Results obtained recently by us (D. De Arriaga, J. Soler & E. Cadenas, unpublished work) are compatible with the proposal that an abortive ternary complex involving enzyme, NAD+ and pyruvate is responsible for this inhibition, in the same manner as proposed by several authors (Sugrobova et al, 1975;Wilton, 1979;Trommer et al, 1979;). Moreover, we found that the inhibitory effect of pyruvate depends also on the temperature, a fact that has been reported for lactate dehydrogenase from several sources (Somero, 1973;Eichner & Kaplan, 1977;Kao & Farley, 1978), and also on NADH concentration in such a way that inhibition of lactate dehydrogenase should increase with an increased concentration of NADH.…”
Section: Discussionsupporting
confidence: 90%
“…NAD(P) is also sensitive to addition of nucleophiles at C-4 of the pyridinium ring (OzoIs and Marinetti, 1969;Everse eral., 197th;Smith, 1976, 1977;Biellman et al, 1979). Several dehydrogenase enzymes catalyse the destructive addition of nucleophiles to NAD (Everse et al, 1971b;Arnold and Kaplan, 1974;Parker, Lodola and Holbrook, 1978;Wilton, 1979;Burgner and Ray, 1984).…”
Section: Preparation Of the Nicotinamide Cofactorsmentioning
confidence: 97%
“…In aqueous solution, the keto–enol equilibrium for pyruvate favours the keto form to a very large extent [70–72]. The rate of enolization, however, is substantial, especially in the presence of a divalent cation, such as ionized calcium or magnesium [73, 74]. Thus, it is conceivable that some of the pharmacological effects of EP are actually mediated by the enol tautomer.…”
Section: Introductionmentioning
confidence: 99%